Marketing Management - Czinkota, Michael R.; Kotabe, Masaaki (Cincinnati : South-Western College Pub., 2001)
A marketing management course shouldn't be treated like a principles class. And an upper-level text doesn't need to be written like an encyclopedia. That's why Marketing Management, 2e takes a direct, "no bull" approach, bringing concepts to life without dry explanations and unnecessary "extra" information. Theoretical and practical considerations are balanced throughout. Coverage of critical and contemporary marketing topics includes integration of e-commerce and a unique chapter on estimating marketing demand.
1. An overview of marketing -- 2. Marketing planning -- 3. Understanding the environment and the competition -- 4. Understanding the buyer -- 5. Marketing research and information -- 6. Estimating the market demand -- 7. Market segmentation, positioning, and branding -- 8. Product and service decisions -- 9. New products -- 10. Pricing decisions -- 11. Distribution and supply chain management -- 12. Designing effective promotion and advertising strategies -- 13. Direct marketing, sales promotion, and public relations -- 14. Selling and sales management -- 15. The future of marketing -- Case 1. Amazon.com -- Case 2. Anheuser-Busch International, Inc. -- Case 3. AT & T -- Case 4. Citibank N.A. in Japan -- Case 5. Kao Corporation -- Case 6. Marketing and the Environment -- Case 7. Pepsi One -- Case 8. Spectrum Color Systems, Inc. -- Case 9. Unisys -- Case 10. Water from Iceland.
Includes bibliographical references and indexes.
PSZ_JB PAGOH SPACE
Keywords: Marketing -- Management; Marketing -- Management -- Case studies